60 PACU Diamond Jubilee : Philippine Association of College & Universities. ([Manila, Philippines] : [publisher not identified], 1992)
"I wish to congratulate the Philippine Association of Colleges and Universities (PACU) on the occasion of its 60th anniversary celebration to be held on November 27, 1992."
Keywords: PHILIPPINE ASSOCIATION OF COLLEGES AND UNIVERSITIES -- 1932-1992